Sex differences in cardiac rehabilitation barriers among non-enrollees in the context of lower gender equality: a cross-sectional study - Mahdieh Ghanbari Firoozabadi; Masoud Mirzaei; Sherry L Grace; Mohammadreza Vafaeinasab; Maryam Dehghani-Tafti; Abbas Sadeghi; Zohre Asadi; Mohammad Hasan Basirinezhad (BMC Cardiovascular Disorders, 2023)
Abstract Background Despite the benefits of cardiac rehabilitation (CR), it remains under-utilized, particularly by women. This study compared CR barriers between non-enrolling men and women in Iran, which has among the lowest gender equality globally. Methods In this cross-sectional study, CR barriers were assessed via phone interview in phase II non-attenders from March 2017 to February 2018 with the Persian version of the Cardiac Rehabilitation Barriers Scale (CRBS-P). T-tests were used to compare scores, with each of 18 barriers scored out of 5, between men and women. Results 357 (33.9%) of the sample of 1053 were women, and they were older, less educated and less often employed than men. Total mean CRBS scores were significantly greater in women (2.37 ± 0.37) than men (2.29 ± 0.35; effect size[ES] = 0.08, confidence interval[CI]: 0.03–0.13; p < 0.001). The top CR barriers among women were cost (3.35; ES = 0.40, CI:0.23–0.56; P < 0.001), transportation problems (3.24; ES = 0.41, CI:0.25–0.58; P < 0.001), distance (3.21; ES = 0.31, CI:0.15–0.48; P < 0.001), comorbidities (2.97; ES = 0.49, CI:0.34–0.64; P < 0.001), low energy (2.41; ES = 0.29, CI:0.18–0.41; P < 0.001), finding exercise as tiring or painful (2.22; ES = 0.11, CI:0.02–0.21; P = 0.018), and older age (2.27; ES = 0.18, CI:0.07–0.28; P = 0.001). Men rated “already exercise at home or in community” (2.69; ES = 0.23, CI:0.1–0.36; P = 0.001), time constraints (2.18; ES = 0.15, CI:0.07–0.23; P < 0.001) and work responsibilities (2.24; ES = 0.16, CI:0.07–0.25; P = 0.001) as greater CR barriers than women. Conclusion Women had greater barriers to CR participation than men. CR programs should be modified to address women’s needs. Home-based CR tailored to women’s exercise needs and preferences should be considered.